Sustainable Energy Planning and Management with PV, batteries, energy management, and user engagement - Østergaard, Poul Alberg; Johannsen, Rasmus Magni; Cabrera, Pedro (International Journal of Sustainable Energy Planning and Management, 2025)
This 44th volume of the International Journal of Sustainable Energy Planning and Management presents contemporary work on photo voltaic (PV) systems – both their resource and economic assessment. Other work explores the use of batteries in renewable energy communities, focusing on their economic feasibility under current conditions as well as development prospects for these. Other flexibility measures are also addressed – however with a focus on use engagement rather than technical options. Lastly, energy savings and energy management in small and medium sized enterprises are addressed in alignment with ISO 50001 standards.